Metformin Role in Diabetic Patients with Tuberculosis: a Review - Esravila Ariya Wibisono (Journal of Tropical Pharmacy and Chemistry, 2021)
Tuberculosis (TB) epidemic is a global health challenge, and WHO estimated the incidence of the new cases reaching 11.1 million people in 2017. Indonesia is classified as a high TB burden country, with 8% of its population infected by TB and ranks third in the world. Type-2 diabetes mellitus (T2DM) is known comorbidity for TB patients. TB-T2DM patients have a higher chance of morbidity, mortality, relapse, bacterial resistance, treatment failure, and slower sputum conversion than TB patients without T2DM. Recent studies suggest that metformin may have a potential synergistic role for TB-T2DM patients. Metformin has immunomodulator properties that can improve the body's immune response and inflammatory response against TB in individuals with T2-DM.